Nitric Oxide and Carbon Monoxide Act as Inhibitory Neurotransmitters in the Longitudinal Muscle of C57BL/6J Mouse Distal Colon - Ayako Hidaka; Yasu-Taka Azuma; Hidemitsu Nakajima; Tadayoshi Takeuchi (Elsevier, 2010)
The present study was designed to identify the inhibitory neurotransmitters mediating nonadrenergic noncholinergic relaxation in the longitudinal muscle of C57/BL mouse distal colon. Relaxation induced by electrical field stimulation (EFS) was recorded isotonically in the presence of atropine and guanethidine. Cyclic guanosine-3',5'-monophosphate (cyclic GMP) content was measured by radioimmunoassay. EFS-induced relaxation was inhibited by nitro-l-arginine (l-NNA) and Sn (IV) protoporphyrin dichloride IX (SnPP-IX), a nitric oxide (NO) and carbon monoxide (CO) synthase inhibitor, respectively. A combination of both inhibitors produced an additive effect. ODQ, a soluble guanylate cyclase inhibitor, inhibited EFS-induced relaxation. NOR-1, a NO donor, and carbon monoxide-releasing molecule-2 (CORM-2), a CO donor, treatment relaxed the distal colon and increased cyclic GMP content. The effects of NOR-1 and CORM-2 were inhibited by ODQ. KT5823, a cyclic GMP-dependent protein kinase inhibitor, inhibited EFS-induced relaxation. EFS-induced relaxation in the presence of KT5823 was further inhibited byl-NNA, but not by SnPP-IX. In addition, KT5823 inhibited CORM-2-induced relaxation, but not NOR-1-induced relaxation. H89, a cyclic AMP-dependent protein kinase inhibitor, inhibited EFS-induced relaxation, and EFS-induced relaxation in the presence of H89 was further inhibited byl-NNA. These results suggested that NO and CO function as inhibitory neurotransmitters in the longitudinal muscle of C57BL mouse distal colon. Keywords:: mouse distal colon, nonadrenergic noncholinergic (NANC) relaxation, nitric oxide (NO), carbon oxide (CO), cyclic guanosine-3',5'-monophosphate (cyclic GMP)-dependent protein kinase